Study of the hygienic-sanitary conditions of beef in tertiary cattle in Puente Lucia, Guayas precinct - Culcay Troncoso, Israel Hernán; Bravo Ponce, Astrid Carolina; Noboa Marín, César Luis; Pérez Campuzano, Leonardo Andrés; Cedeño Reyes, Pedro Pablo (ECOAgropecuaria. Revista Científica Ecológica Agropecuaria, 2024)
Beef is one of the most consumed animal products worldwide, recognized for its high protein and nutrient content. Inadequate processing can generate health risks and foodborne diseases (FBDs), for this reason, it is crucial to guarantee its microbiological quality to save public health. The objective of the study was to identify the presence of pathogenic microorganisms in beef at the Puente Lucia precinct, located in Guayaquil. It focused on detecting microorganisms such as Salmonella spp, Escherichia coli and mesophilic aerobes. The unit of analysis consisted of beef samples from different third parties. The research was developed under a non-experimental, descriptive and observational approach. Surveys were also administered to the owners of the tertiary farms to collect relevant information and provide recommendations on the correct handling of the meat. Samples were collected at five sales points and pooled for shipment to the laboratory, where microbiological analyses were performed. The results revealed the presence of Escherichia coli with an average of 9,552×10³ CFU/g, Mesophilic aerobes with an average of 1,944×10⁶ and Salmonella spp. was not detected in any of the samples analyzed.
Keywords: Beef; public health; quality; sanitary hygiene